The growing impact of lyophilized cell-free protein expression systems. Issue 4 (4th July 2017) - Hunt, J. Porter; Yang, Seung Ook; Wilding, Kristen M.; Bundy, Bradley C.
ABSTRACT: Recently reported shelf-stable, on-demand protein synthesis platforms are enabling new possibilities in biotherapeutics, biosensing, biocatalysis, and high throughput protein expression. Lyophilized cell-free protein expression systems not only overcome cold-storage limitations, but also enable stockpiling for on-demand synthesis and completely sterilize the protein synthesis platform. Recently reported high-yield synthesis of cytotoxic protein Onconase from lyophilized E. coli extract preparations demonstrates the utility of lyophilized cell-free protein expression and its potential for creating on-demand biotherapeutics, vaccines, biosensors, biocatalysts, and high throughput protein synthesis.